2021
DOI: 10.3389/fonc.2021.736620
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Trial of Adjuvant Durvalumab Following Trimodality Therapy for Locally Advanced Esophageal and Gastroesophageal Junction Adenocarcinoma: A Big Ten Cancer Research Consortium Study

Abstract: BackgroundMost patients with resectable locally advanced esophageal and gastroesophageal junction (GEJ) adenocarcinoma (AC) receive concurrent chemoradiation (CRT) followed by esophagectomy. The majority of patients do not achieve pathologic complete response (pCR) with neoadjuvant CRT, and the relapse rate is high among these patients.MethodsWe conducted a phase II study (ClinicalTrials.gov Identifier: NCT02639065) evaluating the efficacy and safety of PD-L1 inhibitor durvalumab in patients with locally advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 43 publications
(48 reference statements)
0
38
0
Order By: Relevance
“…All of the 7 patients (18%) with tumours expressing PD-L1 CPS ≥ 10 were alive at 1 year. Of the 19 patients (51%) with PD-L1 CPS ≥ 1, median OS was significantly superior compared to patients with PD-L1 CPS < 1 (40.4 vs. 25.0 months, p = 0.0132) [75]. Though this study was underpowered due to small study size, it highlights the potential for PD-L1 to be used as a predictive biomarker to immunotherapy in the adjuvant setting for resected OG adenocarcinoma.…”
Section: Programmed Death Ligand-1 (Pdl-1)mentioning
confidence: 76%
See 1 more Smart Citation
“…All of the 7 patients (18%) with tumours expressing PD-L1 CPS ≥ 10 were alive at 1 year. Of the 19 patients (51%) with PD-L1 CPS ≥ 1, median OS was significantly superior compared to patients with PD-L1 CPS < 1 (40.4 vs. 25.0 months, p = 0.0132) [75]. Though this study was underpowered due to small study size, it highlights the potential for PD-L1 to be used as a predictive biomarker to immunotherapy in the adjuvant setting for resected OG adenocarcinoma.…”
Section: Programmed Death Ligand-1 (Pdl-1)mentioning
confidence: 76%
“…Patients who received adjuvant chemotherapy had improved DFS (HR 0.58, 95% CI 0.44-0.72; p < 0.0001) and OS (HR 0.66, 95% CI 0.51-0.85; p= 0.0015) compared to surgery and observation alone. The estimated 5-year OS rate was 78% (95% CI [74][75][76][77][78][79][80][81][82] in the adjuvant capecitabine and oxaliplatin group versus 69% (95% CI [64][65][66][67][68][69][70][71][72][73] in the observation group [26,27].…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%
“…The six trials consisted of five non-randomized trials ( 10 13 , 15 ) and one randomized controlled trial ( 14 ). Two trials were conducted in the United States of America ( 14 , 15 ), three in China ( 10 , 12 , 13 ), and one in the Netherlands ( 11 ). Of the six studies included, two were phase I/Ib trials ( 12 , 13 ), three were phase II trials ( 10 , 11 , 15 ), one was a phase III trial ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous ICI clinical trials have reported promising anti-tumor activity of for the treatment of EC ( 7 9 ). Some attention has been given to the clinical efficacy and safety of combination RT/CRT and ICIs for EC, but further investigation is still needed ( 10 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…In NCT02639065, FFPE samples were used in the Illumina NovaSeq 6000 platform, the primary endpoint was 1 year relapse-free survival (RFS), and 37 patients’ normalized expression data (fragments per kilo base of transcript per million mapped fragments (FPKM)) has been uploaded to NCBI GEO (GSE183924), along with RFS time. Adjuvant durvalumab therapy caused improvement in one-year RFS and was associated with the presence of M2 tumor-associated macrophages (TAMs), along with memory T cells [ 82 ].…”
Section: Datasets With Anti-pd-l1 Monotherapymentioning
confidence: 99%